The production of biopharmaceuticals in Brazil: current issues (Brazilian Journal of Pharmaceutical Sciences, 2019)
Biopharmaceuticals are gaining a growing share of the pharmaceuticals market. In recent years, the Brazilian Health Surveillance Agency (ANVISA) has approved the registration of biological drugs with domestic production. Although Brazil is in the early stages of biopharmaceutical production, governmental incentives and the investment in private companies in the technological domain in this country have created expectations of an increase in the capacity of biopharmaceutical production. Private initiatives, once rare, have now started to blossom in this field, such as collagenase from Cristalia and filgrastim from Eurofarm. The expiry of the patents for certain biopharmaceuticals (e.g. infliximab, filgrastim and rituximab) has generated the possibility of savings to the Brazilian National Health System (SUS) in terms of biosimilars and incentives for national production. National production could also avoid dependence on external imports and a lack of essential supplies. In the next few years, Brazil is expected to bring nationally produced biopharmaceuticals to the market. Although there is some way to go before Brazil will be able to sustain the national demand for biopharmaceuticals and supply international markets with new products, the country is starting to take its first steps towards these objectives.